Sustainability-Driven Valuation: The Role of Capital Structure and Profitability in Firm Value with Corporate Social Responsibility as A Moderator - Cempaka, Putri Ariyani; Simatupang, Frido Saritua (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
This research delves into the ways in which sustainability influences business valuation, in particular analyzing how capital structure and performance impact the value of a firm. This study examines the relationship between financial institutions listed on the Indonesia Stock Exchange (IDX) and the impact of corporate social responsibility as a moderator from 2020 to 2023. Out of 47 banking firms in Indonesia, 16 were selected for the sample using a purposeful selection approach. Panel data regression, in conjunction with software (version 10), was used to analyze secondary data in this study. The findings demonstrated that the FEM analytical model was the best fit. The research shows that capital structure, when considered in isolation, has no effect on firm value. In contrast, a company's worth may be positively impacted by profitability on its own. The financial structure and profitability of a firm have a substantial impact on its value. Furthermore, CSR does not mitigate the association between capital structure and company value, according to the research. Corporate social responsibility does, however, reduce the correlation between profit and company value.